PELAKSANAAN PEMBINAAN GELANDANGAN DAN PENGEMIS OLEH DINAS SOSIAL KOTA PEKANBARU - Andrio Purnama; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Social Service Pekanbaru function is to provide guidance to the Homeless and beggars by providing socialization, skills and decent jobs so that they do not return to beg in the streets, while the types of skills that are given Social Service pekanbaru form, though the skills of food, craft-making skills, the skills to make cakes and skills shoe soles.There are some barriers Social Service Pekanbaru to exercise Homeless and beggars in coaching to guide the Homeless and beggars in because of the limited budget and limited space for development due to the Social Service Pekanbaru not have the permanent place to stop coaching Implementation activities Homeless and beggars.The concept of the theory that researchers use the concept of organizational development coaching goal itself to gain awareness in a person must know himself, herself to be able to change someone better, more advanced, more positive. Without knowing yourself, too difficult or even impossible someone would change himself.This study uses qualitative research methods to study descriptive data. In collecting the data, researchers use interviewing techniques, observation and study of literature. By using key informants and informant as a supplementary source of information.These results indicate that the guidance provided Social Service Pekanbaru is insufficient it can be seen from the number of Homeless and beggars in the city of Pekanbaru lack of permanent shelters for conducting the implementation of the guidance.Keywords: Implementation of coaching Homeless and beggar